2011
DOI: 10.1002/ajh.22045
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for early detection of sickle nephropathy

Abstract: Renal complications affect nearly 30–50% of adults with sickle cell anemia (SCA), causing significant morbidity and mortality. Standard renal function tests like serum creatinine and glomerular filtration rate become abnormal in this disease only when renal damage has become extensive and largely irreversible. Moreover, not all patients develop sickle nephropathy (SN). Therefore, noninvasive biomarkers that predict early onset of SN are necessary. We performed a cross-sectional analysis for nephropathy in 116 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 49 publications
3
66
4
Order By: Relevance
“…20,[52][53][54][55][56][57] KIM-1 is a transmembrane protein whose expression and release by proximal tubular cells is increased after exposure to inflammatory stimuli. 58 Consistent with other studies, 59,60 we observed that concentrations of urine KIM-1 were increased in SCD patients with albuminuria. A unique finding of our study is that KIM-1 concentration significantly correlated with cell-free hemoglobin concentration in the urine of patients with SCD and in the supernatant of HK-2 cells exposed to cell-free hemoglobin.…”
Section: Discussionsupporting
confidence: 91%
“…20,[52][53][54][55][56][57] KIM-1 is a transmembrane protein whose expression and release by proximal tubular cells is increased after exposure to inflammatory stimuli. 58 Consistent with other studies, 59,60 we observed that concentrations of urine KIM-1 were increased in SCD patients with albuminuria. A unique finding of our study is that KIM-1 concentration significantly correlated with cell-free hemoglobin concentration in the urine of patients with SCD and in the supernatant of HK-2 cells exposed to cell-free hemoglobin.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies on renal injury have shown the feasibility of this marker in predicting damage due to acute kidney injury. 30 The chronic nature of kidney damage in b-TM, likely without renal interstitial damage, may explain the normal U KIM-1 values of our patients.…”
mentioning
confidence: 61%
“…Novel biomarkers are under investigation for use in SCD. Urinary kidney injury molecule-1 (KIM-1) and N-acetyl-b-D-glucosaminidase (NAG) presented a strong correlation with albuminuria in a recent cohort of 116 patients with SCD [25]. Urine endothelin-1 was also found to be associated with microalbuminuria in SCD patients, as well as with urinary concentration defect [26].…”
Section: Discussionmentioning
confidence: 99%